Perlindungan Hukum terhadap Hak Anak dalam Memperoleh Akta Kelahiran - Anak Agung Ketut Sukranatha; Anak Agung Istri Ari Atu Dewi (University of Merdeka Malang, 2018)
Children’s problems lately are very complex. Many cases occur in the community that ignore the fulfillment of children’s rights. One is the lack of fulfillment of children’s rights on birth certificates. In connection with this matter, it is important to do research to find out 2 (two) things, namely; first, to find out about children’s rights in obtaining birth certificates to Balinese indigenous people. Second, to find out whether a child can get a birth certificate if the birth registration goes beyond the deadline. In accordance with the research objectives, the research method used isa normative research method with a statue approach. The results of this study are legal protection of children’s rights in obtaining birth certificates in the community has been regulated starting from the 1945 Constitution of the Republic of Indonesia, Law of the Republic of Indonesia Number 23 of 2002 concerning Child Protection, Law of the Republic of Indonesia Number 23 The year 2006 was amended by the Republic of Indonesia Law Number 24 of 2013 concerning the Implementation of Population, Badung Regency Regional Regulation Number 10 of 2010 which was amended by Badung District Regulation Number 9 of 2016 concerning Amendment to Badung Regency Regional Regulation Number 10 of 2010 concerning Implementation Population Administration, Regional Regulation of Denpasar City Number 5 of 2014. Birth Registration that exceeds the fixed time limit can be done by requesting approval from the Head of the Population and Civil Registration Office. The advice can be given 1) socialization is needed regarding the procedures for registering births including procedures for registering online and needing to improve services by the Regional Government. For the community, the need for public awareness of the importance of having a birth certificate as a manifestation of children’s rights in obtaining a birth certificate. How to cite item: Sukranatha, A., Ari Atu Dewi, A. (2018). Perlindungan Hukum terhadap Hak Anak dalam Memperoleh Akta Kelahiran. Jurnal Cakrawala Hukum, 9(1), 1-10. doi:https://doi.org/10.26905/idjch.v9i1.2160